Layanan Konseling Kelompok dengan Pendekatan Rational Emotive Behavior Therapy (REBT) untuk Mengatasi Stres pada Wanita Single Parent - Desi Harlina; Netrawati; Yeni Karneli (Citra Dharma Cindekia, 2022)
This research describes approaches that can be used for single parents to shape their lives. The single parent referred to in this study is a woman or mother as a single parent. The facts that show that single parents have troubling problems are evident in financial, social, and parenting issues. This often results in women whose status as single parents are also responsible for changes in their lives, causing psychological disorders in single parents. One of the psychological disorders experienced is stress. The purpose of this study is to help reduce stress in single parent women by using a group approach. The method used in this research is literature study by utilizing articles, journals, books and supporting documents related to group counseling with the REBT approach in dealing with stress. The findings of this study reveal that using the rational emotive behavior therapy (REBT) approach by means of group counseling is effective in helping single parent women deal with stress.